Renewable Energy for Environmental Protection: Integrated Assessment and Sustainable Development Pathways in Arid Regions of Central Asia - D., Kholov Y.; Sh., Komiljonova; F., Farmonova; Z., Sharipova (American Journal of Bioscience and Clinical Integrity, 2026)
Environmental degradation, climate change, and resource depletion have intensified the need for sustainable energy systems worldwide. Renewable energy is increasingly recognized as a key solution for mitigating environmental impacts and ensuring long-term sustainability. This study provides a comprehensive analysis of the role of renewable energy in environmental protection, with a particular focus on arid regions of Central Asia, including Uzbekistan. The research integrates environmental assessment, climate analysis, and energy system evaluation. The findings indicate that renewable energy significantly reduces greenhouse gas emissions, improves air quality, enhances energy efficiency, and contributes to sustainable economic development. However, barriers such as financial constraints, technological limitations, and institutional challenges remain critical. The study proposes an integrated framework for renewable energy development based on policy support, technological innovation, and regional cooperation.